Gender and Victimization in Margaret Atwood’s Surfacing - Pina Arrabal, Álvaro (The Grove - Working Papers on English Studies, 2019)
Margaret Atwood’s Surfacing (1972), a contemporary classic nowadays, has raised the interest of all kinds of critics. Some of the most remarkable elements in the novel concern feminism, a movement with which the Canadian author has been highly committed. This paper deals with two specific aspects in Atwood’s work in relation to the aforementioned critical approach: gender and victimization. A thorough reading of the novel is thus done in order to detect and subsequently dissect the main instances of both aspects. Special attention is paid to female characters (Anna and the unnamed protagonist), hypersexualized and victimized in the patriarchal microcosms rendered in the story. Keywords: Atwood, feminism, gender, victimization, hypersexualization, patriarchy